13 planets : the latest view of the solar system - Aguilar, David A. (Washington, D.C. : National Geographic, 2011)
Profiles each of the planets in Earth's solar system, including Pluto, Ceres, Eris, Haumea, MakeMake, the sun, the Oort cloud, comets, and more.
"National Geographic Kids.".
Includes bibliographical references (p. 60) and index.
6.8
3-6
Keywords: Planets -- Juvenile literature; Planets; Planets; Solar system -- Juvenile literature; Solar system; Solar system